The effect of photomultiplier tube glass entrance window on plastic scintillator cast sheet photon dosimetry: A Monte Carlo study - Mohamed, N.S.; Aydin, A.; Tajudin, S.M. (2020)
Plastic scintillators are commonly used for medical dosimetry due to the density and effective atomic numbers that are closer to human soft tissue. When a photomultiplier tube (PMT) is used with a thin scintillator, reflected photon and electrons as a result of Compton scattering either inside the scintillator or PMT entrance window, might contribute to a significant source of additional absorbed dose. Monte Carlo simulation was used to study the effect of different PMT window materials on the absorbed dose of a . mm plastic scintillator cast sheet for parallel photon beam energy up to 1 MeV. The additional dose in the plastic scintillator from 400 keV to 1 MeV due to sapphire and lithium fluoride (LiF) glass are increases from 11% to 47% and 8% to 31 %, respectively. Despite of the lower density of Quartz among other materials, Quartz and magnesium fluoride (MgF) demonstrate almost similar trends of additional dose throughout the energies, which is closer to the sapphire. To reduce the unexpected additional dose, a plastic scintillator with a considerable thickness of a PMT window should be adopted for the 'soft-tissue' dose response.